The filmmaker's philosopher : Merab Mamardashvili and Russian cinema - DeBlasio, Alyssa (Edinburgh : Edinburgh University Press : Edinburgh University Press ; Edinburgh University Press, 2019)
Exploring Mamardashvili's extensive philosophical output, as well as a range of recent Russian films, Alyssa DeBlasio reveals the intellectual affinities amongst directors of the Mamardashvili generation - including Alexander Sokurov, Andrey Zvyagintsev and Alexei Balabanov.
CHAPTER 5 Alexander Zeldovich's Target (2011): Tolstoy and Mamardashvili on the Infinite and the Ear -- CHAPTER 6 Vadim Abdrashitov and Alexander Mindadze's The Train Stopped (1982): Film as a Metaphor fo -- CONCLUSION Andrey Zvyagintsev's Loveless (2017): The Philosophical Image and the Possibilities of Fi -- Appendix -- Bibliography -- Index
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Mamardashvili, Merab; Mamardashvili, Merab; Motion pictures -- Russia (Federation) -- History; Philosophy in motion pictures; Philosophie au cinéma.; HISTORY -- Europe -- Russia & the Former Soviet Union; Motion pictures; Philosophy in motion pictures; Russia (Federation); History